2016
DOI: 10.1002/bdra.23494
|View full text |Cite
|
Sign up to set email alerts
|

Childhood cancer in children with congenital anomalies in Oklahoma, 1997 to 2009

Abstract: Background Data-linkage studies have reported an association between congenital anomalies and childhood cancer. However, few studies have focused on the differences in the effect of congenital anomalies on cancer as a function of attained age. We aimed to examine associations between anomalies and childhood cancer as a function of attained age among children born in Oklahoma. Methods Data were obtained from the Oklahoma State Department of Health from 1997-2009 (n=591,235). We linked Vital Statistics records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(67 citation statements)
references
References 36 publications
8
55
4
Order By: Relevance
“…When only non-chromosomal anomalies were considered, the risk estimates generally remained increased, supporting results of other studies indicating an association with childhood cancer diagnosed at different ages, but with a slight decrease in risk with attained age. [5] We also observed increased cancer risk in relation to increasing number of anomalies present, which is consistent with one earlier report. [18] Also consistent with other population-based data linkage studies that examined non-chromosomal anomalies, we observed increased risks of selected cancer types.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…When only non-chromosomal anomalies were considered, the risk estimates generally remained increased, supporting results of other studies indicating an association with childhood cancer diagnosed at different ages, but with a slight decrease in risk with attained age. [5] We also observed increased cancer risk in relation to increasing number of anomalies present, which is consistent with one earlier report. [18] Also consistent with other population-based data linkage studies that examined non-chromosomal anomalies, we observed increased risks of selected cancer types.…”
Section: Discussionsupporting
confidence: 93%
“…[57] Our overall effect estimate for the risk of cancer among children with non-chromosomal anomalies (OR = 1.35) was only slightly attenuated compared to those reported by Janitz et al (HR = 2.50)[5], Botto et al (incidence rate ratio [IRR] = 2.00),[7] and Fisher et al (HR = 1.58).…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations